2008
DOI: 10.1111/j.1440-1584.2008.00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Partnerships to promote mental health of NSW farmers: The New South Wales Farmers Blueprint for Mental Health

Abstract: It is suggested that the NSW Farm Blueprint and the activities being implemented by the NSW Farmers Mental Health Network partners represent a model for implementation of a mental health promotion in identified at-risk Australian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 7 publications
0
32
0
1
Order By: Relevance
“…27 Fragar et al in their New South Wales Farmers Blueprint for Mental Health and well-being identified building local social networks/opportunity as one of the 22 key areas of action leading to pathways to health. 28 Our study lends strength to this position and underscores the important role of support provided by the family network in the long-term care of patients with severe mental illness living in the community. We should end however on a note of caution on this point.…”
Section: Discussionmentioning
confidence: 65%
“…27 Fragar et al in their New South Wales Farmers Blueprint for Mental Health and well-being identified building local social networks/opportunity as one of the 22 key areas of action leading to pathways to health. 28 Our study lends strength to this position and underscores the important role of support provided by the family network in the long-term care of patients with severe mental illness living in the community. We should end however on a note of caution on this point.…”
Section: Discussionmentioning
confidence: 65%
“…The slow onset of the impact of drought contrasts with the immediate effects of extremes such as cyclones and floods. Investigation of modulators of drought‐related stress could inform community‐based strategies for alleviating stress, promote drought preparedness, and guide community and government agencies providing support for people in rural areas 29 . General practitioners are in a unique position to contribute to programs and initiatives for relieving stress related to climate adversity and for supporting farmers experiencing stress 30 .…”
Section: Discussionmentioning
confidence: 99%
“…General practitioners are in a unique position to contribute to programs and initiatives for relieving stress related to climate adversity and for supporting farmers experiencing stress 30 . Educating general practitioners about drought and stress in farming communities, as well as about practical approaches to supporting farmer health and safety, is critical 29 …”
Section: Discussionmentioning
confidence: 99%
“…In the Australian literature, drought is a defining feature of explanations for increases in male farmer suicides (e.g. Judd et al 2006;Berry et al 2011;Alston 2011;Guiney 2012;Hanna et al 2011;Fragar et al 2008;Alston and Kent 2008). Berry et al (2011) suggest that male farmers experiencing long-term exposure to uncontrollable stress, such as that caused by weather impacting on economic conditions, are likely to have deteriorating mental health which in part explains increases in suicide.…”
Section: Introductionmentioning
confidence: 99%